Climate change research in bilateral development programmes: experiences from India and Peru. Issue 3 (3rd April 2019) - Muccione, Veruska; Orlowsky, Boris; Allen, Simon K.; Huggel, Christian; Salzmann, Nadine; Montoya, Nilton; Randhawa, Surjeet Singh; Stoffel, Markus
ABSTRACT: This article reflects on the merits and shortfalls of bilateral research programmes aimed at strengthening climate change research capabilities, using the experience from two programmes, the PACC and IHCAP in Peru and India, respectively. The study highlights key aspects of these types of bilateral programmes, namely: capacity; performance, salary and appreciation; funding; bureaucracy and hierarchy; publishing; and data sharing. Furthermore, it emerged that these programmes would benefit from a more extensive consolidation phase of the research activities and partnership rather than rapidly transferring into out- and up-scaling phases.